Inspeção Térmica de Edifícios Existentes (ITE) - Nádia da Silva Fonte (2012)
The emphasis about this paper is the proposal of a new Technical Buildings Inspection method, based on the used method in Catalunha, Spain. The usefulness about this method is bonded with the conditions evaluation of the existing buildings, which have the purpose of get into leasing market. With the actual country conjecture, the demand for leasing market will grow significantly, which justify the needing to supply information about the conditions of use of fractions. The purposed method intends to verify the used buildings condition and so classify them as enabled or not enabled for the leasing market. The method will also allow verifying what the biggest problems at the habitation, allowing the owner to carry out rehabilitation works, if necessary. As it was already said, this method is based on ITE from Catalunha. However, the method which intends to be purposed will be much more developed, addressing more aspects, such as acoustics and thermics, which are not considered in the Catalan model. It was proceeded also to the application of the proposed methodology to two buildings. The first application will be to a fraction of a single family building, while the second will be to a single family house. At the end of this paper it will be make a critical analysis of the proposed method and their applications. KEYWORDS: rehabilitation, leasing, inspection, buildings, case studies.